1990
DOI: 10.1152/ajpheart.1990.258.6.h1786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemic zone size on nonischemic zone function

Abstract: To study the influence of ischemic zone size on function in nonischemic regions, wall thickening and the end-systolic pressure-thickness (ESPTR) relationship were measured before and during a 90-s coronary occlusion, which produced either a small or large (24 or 35% of left ventricular mass) area of ischemia. With both size ischemic areas, nonischemic zone isovolumic and ejection phase wall thickening increased during occlusion, primarily because of increased preload and, to a lesser extent, a reduced pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…It has been postulated that, during regional ischemia, either a difference in contractility (''weak and strong muscles in series'') or a difference in timing (''asynchrony'') between ischemic and nonischemic regions is responsible for the mechanical interaction (2,16,17,20,23,28). In the present study, we confirmed a role for both mechanisms in regionally stunned myocardium.…”
Section: Underlying Mechanismsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been postulated that, during regional ischemia, either a difference in contractility (''weak and strong muscles in series'') or a difference in timing (''asynchrony'') between ischemic and nonischemic regions is responsible for the mechanical interaction (2,16,17,20,23,28). In the present study, we confirmed a role for both mechanisms in regionally stunned myocardium.…”
Section: Underlying Mechanismsupporting
confidence: 85%
“…During ischemia, three independent factors have been identified to contribute to mechanical interaction: 1) changes in sympathetic tone, 2) the Frank-Starling mechanism, and 3) direct myocardial unloading (2,7,8,10,12,16,17,20,23,28,30). The proposed mechanism to explain mechanical interaction during ischemia is discussed for the present experimental conditions.…”
Section: Underlying Mechanismmentioning
confidence: 83%
“…Whereas regional ischemia is usually associated with an increase in shortening and thickening in the nonischemic region, it is also accompanied by a decrease in the end-systolic performance of the nonischemic region [1, 2]. Not surprisingly, the size of the ischemic bed appears to be the principal determinant of nonischemic end-systolic function [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas regional ischemia is usually associated with an increase in shortening and thickening in the nonischemic region, it is also accompanied by a decrease in the end-systolic performance of the nonischemic region [1, 2]. Not surprisingly, the size of the ischemic bed appears to be the principal determinant of nonischemic end-systolic function [1, 2]. Ischemia of a large area has been shown to be associated with a decrease in nonischemic end-systolic performance as manifested by a leftward and downward shift of the nonischemic end-systolic pressure-thickening relationship [2](fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation